ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS PEMANEN KELAPA SAWIT (KASUS PADA PT SOCFIN INDONESIA PERKEBUNAN AEK LOBA KECAMATAN AEK KWASAN DAN KECAMATAN PULAU RAKYAT KABUPATEN ASAHAN PROVINSI SUMATERA UTARA) - Sriyoto Sriyoto; Andi Irawan; Kianditara Kianditara (Jurnal Agrisep)
This research was aimed to know the productivity level of palm fruit harvesting labours and to know the productivity influence factors of palm fruit harvesting labours at Socfin Indonesia Company Aek Loba Plantation. Productivity of man power was calculated by using productivity analysis and  to identify factors influencing the productivity of palm fruit harvesting labours at Socfin Indonesia Company Aek Loba Plantation.  Eighty seven respondent selected using simple random sampling and data were analyzed using double linear regression analysis.  Result of this research show the productivity of palm fruit harvesting labours at Socfin Indonesia Company Aek Loba Plantation still in lower category, with range of 93,05 – 1884,8 and an average of 759,04 Kg/days. The estimation result show that age, work experiences and family amount responsibility variable have the positive influences to the productivity of palm fruit harvesting labours. Its means that the premi perceptions and work motivation has no real influence to the productivity of palm fruit harvesting labours.